Antibiofilm effects of Limosilactobacillus reuteri 29A cell-free supernatant against major Candida species in murine model of vulvovaginal candidiasis - Boahen, Angela (2023)
Postbiotics are metabolites secreted from live microorganisms in their cell-free supernatants and are strain dependent. They can mimic the beneficial therapeutic effects of probiotics while avoiding the risk of administering live microorganisms, coupled with having longer shelf-life. Lactic acid bacteria (LAB) such as Lactobacillus species which are commonly employed as probiotics, are native members of a healthy vaginal microbiota, and their dominance is crucial for an eubiotic vaginal ecosystem. They confer protection through various mechanisms including production of postbiotics. One of the major disorders affecting vaginal health is vulvovaginal candidiasis (VVC) and its reoccurrence, caused by Candida species including Candida albicans and Candida glabrata. The aforementioned Candida species, notably C. albicans is a biofilm producing pathogen and habitually forms part of the vaginal microbiota. Latest research has implicated the role of fungal biofilms in VVC, particularly in the setting of treatment failure and recurrence. Hence, in this study, we aimed to evaluate the antibiofilm activity of postbiotics produced by Limosilactobacillus reuteri 29A, in vitro and in VVC murine model. The cell-free supernatant (CFS) was derived from fresh 48 h anaerobically cultured L. reuteri 29A strain in De Man, Rogosa and Sharpe (MRS) broth. It was filter sterilized before introducing to preformed biofilms of C. albicans (ATCC 14053), C. glabrata (ATCC 2001) reference isolates and C. albicans (S.21), C. glabrata (95670) clinical isolates. Specifically, L. reuteri 29A CFS destroyed 91% of C. albicans ATCC 14053 and 92% of C. albicans S.21 biofilms. For C. glabrata isolates, L. reuteri 29A CFS inhibited 86% of ATCC 2001 and 83% for C. glabrata 95670 biofilms. The mechanism of the CFS was dependent on its low pH level. Metabolites produced in L. reuteri 29A CFS were identified by Gas Chromatography-Mass Spectrophotometry. Scanning electron microscopy (SEM) displayed the destruction of preformed biofilms and impediment of C. albicans morphogenesis after postbiotics administration in vitro. The present study also aimed to investigate the role of the CFS in VVC murine model. BALB/c female mice were inoculated intravaginally with cell suspensions of the clinical isolates of Candida species before treatment with L. reuteri 29A CFS. Microbiological and cytological examinations revealed that C. albicans yeast to hyphae formation was inhibited and prohibited after L. reuteri 29A CFS administration, via eliciting the hosts immune response. Histopathological examination revealed the formation of Candida species biofilms on the vagina epithelium. However, after treatment with L. reuteri 29A CFS, desecrated vaginal tissues were restored through Candida species biofilm inhibition. SEM in vivo further displayed the reinstatement of a bacterial microflora. Colony forming unit count showed the reduction of fungal burden in infected mice after L. reuteri 29A CFS administration. Although the efficacy of the postbiotics L. reuteri 29A has been proven in in vitro and murine model, its limitation includes its application among human subjects. Overall, the results of this study demonstrate the potential use of the postbiotics of L. reuteri 29A as an adjuvant to treat and/or prevent Candida related vaginal infections.